Jamaica SME Finance : Technical Note - World Bank; International Monetary Fund (Washington, DC, 2015)
Almost all formal small and medium enterprises (SMEs) in Jamaica have access to checking or saving accounts, but the financial sector is scarcely used to finance their investments. The lack of funding for the SME sector, or its high cost, has a negative impact on entrepreneurship and business profitability and stability through the business life-cycle, having a particularly negative effect on employment. In addition, the supply of formal nonbank sources of finance is limited, especially for micro-entrepreneurs, with credit unions providing mostly consumer finance and an underdeveloped microfinance sector. The authorities aim to develop a micro-credit act to make it mandatory for multilateral investment funds (MIFs) to register, and to create a regulatory authority to oversee microfinance institution (MFIs). The authorities have taken significant initiatives to enhance the legal and regulatory environment and financial infrastructure, but further efforts are needed. The authorities have also put in place public programs for micro, small, and medium sized enterprise (MSME) finance, however they lack sufficient coordination, and the partial credit guarantee scheme needs to be revamped. It also operates a partial credit guarantee scheme, which is not being utilized by lenders. Thus, its design should be reviewed and revamped to ensure adequate incentives for lenders to use it and its sustainability.